MENINGKATKAN KETERAMPILAN KOMUNIKASI LINTAS BUDAYA MELALUI DRAMA: PENDEKATAN BUDAYA MELAYU DAN INGGRIS DI SMAN 2 RAMBAH HILIR - Eripuddin, Eripuddin; Rahayu, Pipit; Nurazima Juhastri, Azi; Ummi, Rodiatul (Mejuajua: Jurnal Pengabdian pada Masyarakat, 2025)
This community service program aimed to enhance students’ intercultural communication skills through drama training based on Malay and English cultural elements at SMAN 2 Rambah Hilir, Rokan Hulu Regency, Riau Province. The initiative was motivated by the students’ limited English-speaking abilities and the lack of cultural integration in language learning. The implementation employed a participatory and collaborative approach consisting of three main stages: (1) preparation and module development, (2) cultural workshops and training, and (3) intercultural drama performances. The results demonstrated a significant improvement in students’ communication skills, confidence, and intercultural awareness. The drama performance served as an effective and enjoyable learning medium while strengthening students’ appreciation of local Malay cultural identity. Additionally, the program produced a training module that can be utilized by teachers for sustainable learning. Thus, this activity proves that integrating arts, culture, and language in education can effectively foster the development of Pancasila Student Profiles who are creative and globally minded.